Analysis of interaction patterns and tutor assistance in processes of joint reflection in pre-service teacher education. Issue 4 (8th August 2019) - Martinez, Agurtzane; Agirre, Nerea; López-de-Arana, Elena; Bilbatua, Mariam
ABSTRACT: The great majority of teacher training programmes incorporate reflective practice as a fundamental professional competence since reflection is considered to be a key element in professional development. However, in the literature reflection is conceptualised in multiple ways, making it difficult to determine what types of contexts facilitate the activity of joint reflection. The present study aims to shed light on this debate, identifying the strategies of educational assistance given by tutors to a group of students during the process of reflection. To this end, we analyse the interactive dynamics and educational assistance in two cases of joint reflection between tutors and students (10 students in Case 1 and 13 in Case 2). In each case, five sessions, each lasting approximately one hour, were recorded and analysed. Different phases in the process of reflection were identified, as were different specific types of assistance to address joint reflection. In both cases, the assistance of the tutor was found to be necessary in collective scaffolding for the establishment of relationships between situational and academic representations, even though the data suggest a progressive increase in the students' control of the task.